Repeated Batch Fermentation For Lactic Acid Production By Enteroccocus Faecium In Liquefied Sago Starch - Nolasco-Hipolito, Cirilo; Zarrabal, Octavio Carvajal; Kopli, Bujang; Rubena Mafia, Kamaldin; Samuel, Lihan; Ling, Teck Yee (AMB Express, 2012)
Enterococcus faecium No. 78 (BIOTECH 10375) isolated from puto, a type of fermented rice in the Philippines was used to produce lactic acid (LA) in repeated batch fermentation (RBF) mode. Enzymatically liquefied sago starch (LSS) was used as the sole carbon source. LSS was inoculated with E. faecium to perform the saccharification and fermentation processes simultaneously. Results demonstrated that E. faecium was reused for up to 11 fermentation cycles with an average LA yield of 36.3 g/L obtained in 15 hrs at the end of the log phase with the ability to produce 42.5 g/L LA in 30 hrs. By using RBF mode the strain was able to maintain a volumetric productivity of 1.96±.0.241 g/Lh during more than 280 hrs of fermentation. Work is in progress to maintain and increase the usability of the cells over higher fermentation cycles.